Capacity Building of Indonesian Migrant Workers in Korea for Post-Contract Preparation - Cahyati, Widya Hary; Bahatmaka, Aldias; Putriningtyas, Natalia Desy (Jurnal Abdimas, 2024)
Indonesian Migrant Workers (PMI) are Indonesian citizens working abroad. To meet economic needs, many Indonesian citizens choose to work abroad. The problem found in this service activity is that working abroad has many consequences, one of which is being away from family. However, if they return to Indonesia, Indonesian Migrant Workers (PMI) have concerns about the skills they have to work in Indonesia. For this reason, the solution offered to partner problems is socialization related to digitalization of entrepreneurship through the use of social media, as well as ways to market business products. The purpose of this activity is to increase PMI's capacity as a provision for preparation to make a living after the employment contract in Korea has ended. Thus, PMI can work in Indonesia and be close to family. The method of implementing the activity is to provide socialization with the target to the Indonesian Student Association (PPI) and Indonesian Migrant Workers (PMI) in Korea. The result of this service activity is an increase in knowledge, skills, and motivation from the participants, namely PPI and PMI. In addition, it also received a positive response from all participants. This socialization activity is expected to be carried out to Indonesian migrant workers in other countries.